Circulating (1 → 3)-β-D-Glucan as an immune activation marker decreased after ART in people living with HIV - Xun, Jingna; Guo, Shuyan; Xu, Yumin; Chen, Rong; Tang, Qi; Zhang, Xinyu; Liu, Danping; Zhang, Renfang; Shen, Yinzhong; Liu, Li; Wan, Jiangrong; Chen, Jun; et al. (Frontiers in Public Health, 2022)
Background Plasma level of polysaccharide (1 → 3)-β-D-Glucan (βDG), as a diagnostic marker of invasive fungal infection has been reported to be elevated in people living with HIV (PLWH). We assessed the association of circulating βDG to inflammation and systemic immune activation and the effect of antiretroviral therapy (ART) on βDG in PLWH. Method Plasma and peripheral blood monocular cell samples from 120 PLWH naive to ART and after 1 year's ART were collected. Plasma levels of βDG, markers of bacterial translocation, gut damage, and cellular immune activation were quantified. Result The plasma βDG levels were negatively correlated with CD4+ T cells count (r = −0.25, p = 0.005) and positively with HIV viral load (r = 0.28, p = 0.002) before ART. It was also positively correlated with immune activation markers, including PD-1 expression on CD4+ T cell (r = 0.40, p = 0.01) and CD8+ T cell (r = 0.47, p = 0.002), as well as HLADR+CD38+ co-expression on CD8+ T cell (r = 0.56, p = 0.0002), but not with the plasma levels of LPS (r = 0.02, p = 0.84), LPS binding protein (LBP, r = 0.11, p = 0.36), soluble LPS receptor sCD14 (r = 0.04, p = 0.68), intestinal fatty acid binding protein (IFABP, r = −0.12, p = 0.18), and regenerating islet-derived protein 3α (REG3α, r = 0.18, p = 0.06). After 1 year's ART, the levels of βDG were significantly decreased compared to that in pre-ART (1.31 ± 0.24 Log10 pg/ml vs. 1.39 ± 0.18 Log10 pg/ml, p < 0.001). Conclusion The level of plasma βDG was associated with cellular immune activation and decreased after ART in PLWH, suggesting it could serve as a biomarker of immune activation and efficacy monitoring.